Exploration of a community pharmacy delivered mobile health intervention to support medication taking for patients with multiple long-term conditions. (30th November 2022) - Donovan, G; Wilkes, S; Ling, J; Smith, F
Abstract: Introduction: Up to half of people with long-term conditions (LTCs) do not take their medicines as prescribed. Mobile health interventions, such as text messaging, have been shown to have positive impact on medication adherence. 1 However, interventions for patients with multiple LTCs are lacking, and there are limited examples of their delivery from community pharmacy settings. We have developed a new intervention which combines a pharmacist consultation and automated two-way text messaging to support medicines taking. This has been developed using peer-reviewed literature and focus groups with patients and healthcare professionals (GPs, pharmacists, nurses). The intervention is tailored to the individual using a questionnaire and delivers content for up to eight LTCs. Aim: To explore the acceptability of our new intervention with patients. Methods: The new intervention was delivered to patients in a simulated environment, including a consultation with a pharmacist and two weeks of text messaging. Diary-interviews were used to gather feedback from eight patients, recruited through a public, patient and carer involvement group based at a university. Patients kept a diary during the period of text messaging and follow-up semi-structured interviews were conducted. Interviews were audio recorded and transcribed verbatim for analysis. Transcripts were coded for aspects of the intervention that the patients liked and ideas on how the intervention could be changed, including the impact of delivering the intervention from community pharmacies. Ethical approval for this study was granted by the University of Sunderland Research Ethics Committee. Results: The intervention had good acceptability with patients. Patients were happy to interact with the text messaging content, including providing information about symptoms of their long-term condition and result of home monitoring. Patients liked that the intervention was linked to a pharmacist consultation, where there were opportunities to identify medication issues which text messaging could not solve. Delivering the intervention from a community pharmacy setting was felt to promote stronger engagement with the text messaging component, including the opportunity to build rapport with the pharmacist who would be overseeing the intervention. The mechanism to monitor medication adherence using two-way text messaging was suggested to be made more streamlined, and patients also wanted more examples of text message responses included in the patient information leaflet for the intervention. Discussion/Conclusion: We found that our intervention to support medication taking from community pharmacies has initial acceptability with patients. Whilst others have trialled similar technologies from community pharmacies 2 our intervention focussed solely on medication taking, and this seemed to result in positive attitudes towards its delivery from community pharmacies. The consultation was found to be an important component alongside the text messaging, how combining digital and non-digital components work together to support medication adherence was a gap highlighted in our previous review of similar interventions. 3 Our intervention now requires changes based on the feedback gathered in this study and further testing in a larger and more diverse group. References: 1. Thakkar J, Kurup R, Laba T-L, Santo K, Thiagalingam A, Rodgers A, et al. Mobile Telephone Text Messaging for Medication Adherence in Chronic Disease: A Meta-analysis. JAMA Intern Med. 2016;176:340–9. 2. Cork T, Sanzeri D, Chambers R, Chamber C. Can pharmacists promote self-care using digital technology? Prescriber. 2018;29:21–4. 3. Donovan G, Hall N, Ling J, Smith F, Wilkes S. Influencing medication taking behaviors using automated two-way digital communication: A narrative synthesis systematic review informed by the Behavior Change Wheel. Br J Health Psychol. n/a n/a. https://doi.org/10.1111/bjhp.12580 .